Performance of 2019 EULAR/ACR classification criteria for systemic lupus erythematosus in a paediatric population—a multicentre study. (9th February 2021) - Levinsky, Yoel; Broide, Mor; Kagan, Shelly; Goldberg, Ori; Scheuerman, Oded; Tal, Rotem; Tirosh, Irit; Butbul, Yoni; Furst, Daniel E; Harel, Liora; Amarilyo, Gil
Abstract: Objectives: The European League Against Rheumatism and American College of Rheumatology 2019 (EULAR/ACR-19) criteria for the diagnosis of SLE were recently published, with the stated goal of maintaining the level of sensitivity and raising the level of specificity for classification of SLE in adults. The aim of this study is to examine their application to juvenile SLE (jSLE) patients. Methods: In this multicentre study the charts of jSLE patients from three tertiary medical centres were reviewed and compared with patients with non-jSLE diagnosis. Paediatric rheumatologists, blinded to the original diagnosis, reviewed and diagnosed all cases. Paediatric patients' clinical and laboratory data were retrospectively extracted and then examined with regard to how they met the new and old criteria. Results: Included were 225 patients (112 jSLE, 113 non-SLE). When applied to juvenile SLE classification, the sensitivity of the new EULAR/ACR-19 criteria was 0.96 (95% CI: 0.9, 0.99) and the specificity was 0.89 (95% CI: 0.82, 0.94). These were comparable to the SLICC criteria. The sensitivity of the EULAR/ACR-19 criteria improves over time and was 0.83 12 months following disease onset, reaching 0.96 after longer than 24 months. Conclusion: Among a cohort of jSLE patients, sensitivity of the new EULAR/ACR-19 criteria was found to be high and specificity may have improved slightly compared with the SLICC-12 criteria. We support the use of the new classification criteria for paediatric patients in future jSLE studies, but it should be noted that its specificity is lower than for adults.